Strategi Pengembangan Terhadap Pelayanan Di Desa Wisata Keranggan Terkait Kepuasan Pengunjung - Setiawan, Ozi; Riyani, Syafrida Chinta (Institut Seni Indonesia Padangpanjang, 2024)
Keranggan Tourism Village is a tourist village that has great potential as a leading tourist destination in Indonesia. However, these tourist destinations each have many challenges that need to be developed further in order to attract the attention of tourists as part of supporting efforts to satisfy visitors. This research aims to identify effective development strategies in increasing the satisfaction of tourists visiting the Keranggan Tourism Village. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation and literature study. The research results show that infrastructure development, improving the quality of services developed through elements of the Sapta Pesona aspect, appropriate promotional strategies, managing tourist attractions, and active involvement of local communities are key factors in increasing visitor satisfaction. It is hoped that the holistic implementation of interrelated strategies can boost the attractiveness of the Keranggan Tourism Village and make it a sustainable and highly competitive tourist destination.